Capacity-building barriers to S3 implementation: an empirical framework for catch-up regions. Issue 1 (2nd January 2019) - Papamichail, George; Rosiello, Alessandro; Wield, David
Abstract : In this paper, we investigate the implementation challenge of Smart Specialisation Strategies (S3) in catch-up regional environments, through the lens of capacity building. We analyse capacity building at two levels: micro-level (individual organisations) and meso-level (regional inter-organisational networks). We use empirical evidence from 50 interviews conducted in the period 2015–2017 from two Greek regions dramatically hit by the economic crisis (Crete and Central Macedonia). We argue that in the Cretan and Central Macedonian context, the difficulty of implementing S3 is directly linked with firms' lack of adsorptive capability to exploit university-generated knowledge, university knowledge that is too abstract for firm's to easily acquire, as well as to the capability of regional actors to build inter-organisational networking that fits their strategic needs.